PENGARUH NET PROFIT MARGIN, DEBT TO EQUITY RATIO DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN PT. KALBE FARMA TBK TAHUN 2012-2020 - Elfrida Nurbaitti; Sunartiyo (Jurnal Ekonomi dan Industri, 2021)
The results of this study indicate that partially net profit margin has no effect on firm value, Debt to equity ratio does not have a positive effect on firm value and interest rates have a significant positive effect on firm value. And simultaneously net profit margin, debt to equity ratio, and interst rates simultaneously. Simultaneously the relationship between net profit margin debt to equity ratio, and interest rates is influential on firm value, and the probability value on the test results is smaller than the significance level, this means that Ho is rejected, H1 is accepted.